Steroid sensitive nephrotic syndrome as a potential contributor to pediatric-onset psychosis: a case-based hypothesis - Parikh, Parinda; Reddy Dadem, Ananya; Wubuli, Dilnuer; Gultekin, Isa; Narravula, Rithika; Chandra-Kaushik, Arushi; Chandra, Avish; Buddhavarapu, Ishant; Oza, Mina (International Journal of Research in Medical Sciences, 2025)
Steroid-sensitive nephrotic syndrome (SSNS) is a type of primary glomerulopathy that results in multiple complications, including edema and hyperlipidemia. Most existing studies indirectly attribute psychiatric manifestations in SSNS to corticosteroid therapy, while its etiological role in neuroinflammation remains rarely discussed. This article aims to explore this association through a unique case report. An investigation of available English-language literature providing insight into pathophysiology of SSNS, neuroinflammation, and psychosis was done. Information collected was reviewed and analysed for quality and relevance. We present a rare case of a 13-year-old male with SSNS, who exhibited escalating oppositional behavior, emotional dysregulation, and aggression, resulting in a parental request for discontinuation of steroids and immunosuppressants. Despite cessation of medication, symptoms progressed to worsening of psychosis with multiple psychiatric hospitalizations, raising concerns for a potential link between SSNS and neuropsychiatric origin. Collateral history revealed discontinuation of immunosuppressant therapy in early childhood, indicating its limited significance in the current presentation. This case elucidates the potential correlation between SSNS and psychosis in pediatric patients from a pathophysiological and neuropsychiatric point of view, necessitating further investigations into its underlying mechanism.